Reviving Makerere University to a Leading Institution for Academic Excellence in Africa - Tabaire, Bernard; Okao, Jackie (ACODE, 2010)
Established in 1922 as a technical school, Makerere University is now one of the largest universities in eastern and central Africa with 20 faculties/institutes/schools offering not only day but also evening and external study programmes to a student body of more than 30,000 undergraduates and 3,000 postgraduates. It is also a centre of research.
Keywords: Academic Excellence; Leading Institution; Reviving